(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The organizational culture as a social phenomenon and an attribute of the culture of society has been a subject of research for many years. The need for knowledge in the organizational culture increases with the dynamic increase in the expectations of citizens, society and the state. Thanks to the work of a number of prominent scientists, a solid theoretical and methodological basis for conducting research in the field of measuring and evaluating the organizational culture of social organizations was created. This foundation provided the necessary impetus for conducting a research at the Latvian College of Culture. This study shares the belief that organizational culture is a major factor in changes in social organizations that needs scientific understanding and research. Its essence is to build a new organizational culture to ensure the desired organizational behavior. A key issue of a number of research in recent years is how to build the desired profile of this culture. It is of particular importance that this is done in the context of the changes. That is why the organizational culture of all organizations in the culture sector is subject to special attention, and the disclosure of its profile is a topical and significant scientific issue that needs a solution. The study suggests that, by diagnosing the organizational culture of the College of Culture with an appropriate method and toolbox, new knowledge will be gained on how the organizational behavior of Latvian culture college people can be changed in order to increase its efficiency. We are convinced that, without a major change in the organizational culture, there is little chance of permanent positive changes. The survival paradigm of Latvia Culture College is creative and opened environment of the autonomous educational institution created by teachers and students. Such environment is basic guarantee for professional educating of creative, full with initiative and opened to society, loyal culture specialists.